Socio-Health Determinants of Occurrence of Postpartum Hemorrhage Among Women of Reproductive Age 15-49 Years - Kenya (International Journal of Scientific Research and Management (IJSRM), 2021)
SOCIO-HEALTH DETERMINANTS OF OCCURRENCE OF POSTPARTUM HEMORRHAGE Postpartum hemorrhage is the blood loss of 500 ml or more within 24 hours after birth. It is the number one direct cause of maternal mortality Worldwide and constitutes 73% of all the obstetric hemorrhage globally. In Low-income Countries such as Sub-Saharan Africa bears the greatest burden of postpartum hemorrhage. Thirty-four percent of maternal deaths occurring in Kenya are due to postpartum hemorrhage. In Homa Bay County, postpartum hemorrhage is the leading cause of maternal mortality contributing 38% of all maternal deaths despite several strategies by the ministry of health to reduce occurrence. Previous studies attribute this to poor provision and utilization of essential health services. The possible contextual contribution of health system management on occurrence of postpartum hemorrhage has not been explored in the County. The objective of this study was to establish the socio-health determinants of occurrence of postpartum hemorrhage among women of reproductive age 15-49 years in Homa Bay County. The specific objectives were: to identify the socio-demographic determinants of occurrence of postpartum hemorrhage among women of reproductive age; and to determine the personal health determinants of occurrence of postpartum hemorrhage among women of reproductive age. This was a cross-sectional study design in which qualitative and quantitative methods were used. The target population was postnatal women who delivered at the level four public hospitals in Homa Bay County. The sample size was 400 postnatal women. Quantitative data was collected using a structured for socio-demographics determinants, and personal health determinants. Qualitative data was collected using Key Informant Interview guides administered to the eight Sub County Medical Officers of Health and the one County Gynecologist and was recorded. This data was managed thematically while quantitative data was cleaned manually and electronically. The Statistical Package for Social Sciences (SPSS) was used for data processing and analysis. The first stage was processing and analysis involving computation of frequencies and percentages and generation of tables followed by the binary logistic regression for bivariate variables to determine the relationship, adjusted Odds Ratio to determine the degree of significance at a confidence interval of 95% and P-value for each category of the variables. Thematic approach guided the analysis of qualitative data. Socio-health determinants were found statistically significant with multiple logistic regression chi-square 62.08 (P-Value=0.01. The findings had constructing and reviewing programs for women of reproductive age focusing on start of ANC at 1st trimester, age at first both, and the general socio-demographic characteristics through strengthening of community health strategy to improve social and personal health characteristics.